Odpowiedzi

2010-03-27T17:31:08+01:00
A)2x - x + 4,5= 8,5
x=8,5-4,5
x=4
b)2 ( 2x +1) = 8
4x+2=8
4x=8-2
4x=6 /:4
x=1,5
c)x+4 (3x - 5)=7
x+12x-20=7
13x=7-20
13x=-13/:13
x=-1
d)3x-2(x+5)= -1
3x-2x+5=-1
x=-1-5
x=-6
e)2(x+1) -4x= 1
2x+2-4x=1
-2x=1-2
-2x=-1/:-2
x=0,5
f)4(x-1/2)=-6
4(x-0,5)=-6
4x-2=-6
4x=-6+2
4x=-4/:4
x=-1
2010-03-27T17:32:59+01:00
A) 2x - x + 4,5= 8,5
2x-x=8,5-4,5
x=4

b) 2 ( 2x +1) = 8
4x+2=8
4x=8-2
4x=6/:4
x=1,5

c) x+4 (3x - 5)=7
x+12x-20=7
x+12x=7+20
13x=27/:13
x=27/13=2 1/13


d) 3x-2(x+5)= -1
3x-2x-10=-1
3x-2x=-1+10
x=9

e) 2(x+1) -4x= 1
2x+2-4x=1
-2x=1-2
-2x=-1/:(-2)
x=0,5

f)4 ( x - 1/2 ) = -6
4x-2=-6
4x=-6+2
4x=-4/:4
x=-1


2010-03-27T17:37:56+01:00
A)
2x-x+4,5=8,5
x+4,5=8,5/-4,5
x=4
b)
2(2x+1)=8
4x+2=8
4x=6/:4
x=6/4
x=1,5
c)
x+4(3x-5)=7
x+12x-20=7
13x=27/:13
x=27/13
x=2 1/13
d)
3x-2(x+5)=-1
3x-2x-10=-1
x=9
e)
2(x+1)-4x=1
2x+2-4x=1
-2x=-1/*(-1)
2x=1/:2
x=1/2
f)
4(x-1/2)=-6
4x-2=-6/+2
4x=-4/:4
x=-1